Rotas de internacionalização da inovação brasileira na área de saúde: convergências e divergências demonstradas por patentes em tecnologia médica - Guimarães, Márcia Rujner (2019)
This study aims to assess the degree of Brazilian innovation in healthcare generated by the domestic market and its ability to internationalize. Motivated by the importance that knowledge and information currently have, as well as their respective use as a bargaining chip, the research researcher intends to demonstrate that the search for the internationalization of innovation can be the key to success for the competitiveness of organizations, including within international Business. Through tangible innovation in the form of patent, one of the most relevant assets of Intellectual Property, results are little explored in the literature affects the internationalization of Brazilian innovation in health. Therefore, the mapping of the routes taken by such innovations, supported by patents, may generate indicators that aim to contribute to this process in an emerging economy. The dissertation was based on an exploratory, descriptive and causal research, using two methods: descriptive quantitative research based on secondary data and an exploratory qualitative research based on the multiple case study method, based on Albert Einstein Hospital. The result of this study is the finding of great asymmetry in the number of patents researched among the organizations collected in the sample. As a contribution, it is expected that the important findings might stimulate new research on the subject in order to ascertain, in greater depth, the existing gap between the production of innovation generated in Brazil, health, and its consequent internationalization aimed at development of new business models focused on providing more effective solutions for organizations and society.